Modernizing Divorce in Courts: How to Realize Justice in Diverse Geographical Conditions? - Lisnawati, Lisnawati; Ahmad, Sabarudin; Safrut, Bariah (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
The modernization of Islamic family law requires divorce to be carried out in court. However, it causes problems of injustice in its implementation, especially for some people in Central Kalimantan Province. For example, a wide geographical condition makes the location of the court and the community not always easy to reach, which makes it difficult for people to propose and administer divorce through the court. The study aimed to analyze how to realize divorce justice in court in diverse geographical conditions. The study was a juridical-empirical legal study with analysis using the theory of legal objectives and maslahah. The findings showed that divorce in court in its implementation causes injustice, especially in Central Kalimantan Province, due to geographical conditions that make it difficult for people to access the court. The wide area and far distance, and the condition of terrain (broken road) in some areas make the community fall into a dilemma. They must choose the least mudharat (disadvantage/harm). Also, the findings offer optimization of two things that can minimize harm and injustice for the community, namely optimization of the implementation of mobile courts and the use of the e-Court system. The alternative solution is proposed because these two things have limitations in both facilities and infrastructure and their implementation. In addition, it needs to have further study on the idea of isbat talak as another alternative to overcome this problem